2011
DOI: 10.1371/journal.pone.0028132
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biogeography of Public Restroom Surfaces

Abstract: We spend the majority of our lives indoors where we are constantly exposed to bacteria residing on surfaces. However, the diversity of these surface-associated communities is largely unknown. We explored the biogeographical patterns exhibited by bacteria across ten surfaces within each of twelve public restrooms. Using high-throughput barcoded pyrosequencing of the 16 S rRNA gene, we identified 19 bacterial phyla across all surfaces. Most sequences belonged to four phyla: Actinobacteria, Bacteriodetes, Firmicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
311
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(343 citation statements)
references
References 41 publications
25
311
3
4
Order By: Relevance
“…Studies on aerosol generation by modern flush toilets found that up to 145,000 droplets less than 2 µ m in size can be produced per flush 26 Many studies have detected microorganisms in ambient air in bathrooms and on the toilet surface, indicating the production of bioaerosols and the potential for disease transmission. [27][28][29][30][31] Microorganisms have been detected in air 90 minutes after flushing and 25 cm above the toilet seat. These aerosolized microorganisms can maintain their viability and spread in ambient air.…”
Section: Potential For Aerosol Transmission Via Wastewatermentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on aerosol generation by modern flush toilets found that up to 145,000 droplets less than 2 µ m in size can be produced per flush 26 Many studies have detected microorganisms in ambient air in bathrooms and on the toilet surface, indicating the production of bioaerosols and the potential for disease transmission. [27][28][29][30][31] Microorganisms have been detected in air 90 minutes after flushing and 25 cm above the toilet seat. These aerosolized microorganisms can maintain their viability and spread in ambient air.…”
Section: Potential For Aerosol Transmission Via Wastewatermentioning
confidence: 99%
“…These aerosolized microorganisms can maintain their viability and spread in ambient air. 28,29,31,32 The potential for EBOV to spread via this route is not known. Previous studies have focused mainly on bacteria rather than viruses, and they have not measured the full range of aerosol sizes produced by flush toilets.…”
Section: Potential For Aerosol Transmission Via Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…16 Primers were designed for use with the GS Junior system (454 Life Sciences, Branford, CT, USA). Adaptors and multiplex identifiers (MIDs) were included in primer sequences which were purchased from Eurofins Genomics laboratories (Ebersberg, Germany).…”
Section: S Rrna Gene Sequencingmentioning
confidence: 99%
“…12,13 It has been shown that human occupants leave a distinct human microbial fingerprint indoors, and different room types and surfaces will have different fingerprints depending on their specific use. [14][15][16] Heating, ventilation and air conditioning (HVAC) systems are necessary for meeting energy and air quality demands in modern buildings. These systems transport large quantities of air into and out of buildings and have extensive inner surface areas in the form of ventilation ducts and filters.…”
Section: Introductionmentioning
confidence: 99%